Solidification and phase formation of alloys in the hypoeutectic region of the Fe–C–B system. (15th October 2015) - Lentz, Jonathan; Röttger, Arne; Theisen, Werner
Graphical abstract: Abstract: In this work, alloys from the hypoeutectic iron-rich region of the iron–carbon–boron (Fe–C–B) system were investigated with respect to the solidification and the phase formation. Laboratory melts with a constant carbon content of 0.6 mass% and boron contents of 0.2 mass%, 0.6 mass%, and 1.8 mass% were fabricated and metallographically examined. In addition the microstructures were investigated by CALPHAD method in the state of equilibrium and by multiphase-field (MPF) method to reproduce the non-equilibrium process of the technical solidification. The results were analyzed with respect to the effect of boron on the solidification paths, microstructural crystallization processes as well as the morphological and chemical characteristics of the solidified phases. The investigated alloys undergo primary crystallization of austenite (γ-Fe). Due to the low solubility of B in the primary phase γ-Fe, B is strongly segregated in the melt and the solidification paths are deviated to high B contents. Therefore, as the B content increases, the eutectic solidification sequence starts with the B-rich Fe2 B phase and continues with the formation of the B-rich Fe3 (B, C) phase in the latter process. The B content of the melt thus decreases during the eutectic reaction, and the eutectic Fe3 (B, C) phase exhibits a decreasing B gradient in the direction of growth. Consequently, the low-melting phase of the Fe–C–B system is the Fe3 (B, C) phase with a low B content and a composition closest to its low-melting B content of 14.10 at.% B. Increasing B/(C + B) ratios of the alloy composition raise the average B content of the Fe3 (B, C) phase (up to >20 at.% B) and hence at the same time increase the solidus temperature of the alloy. These findings revealed consistency with experimental results for chemical composition (WDX), phase analysis (diffraction with synchrotron radiation, EBSD), and thermal analysis (DTA).